Venetoclax for elderly patients with acute myeloid leukaemia unfit for intensive chemotherapy: Prospects, resistance mechanisms and management strategies - Jinlin Zhang; Jile Liu; Mohan Zhao; Xiaoyu Zhang; Linlin Liu; Mengnan Li; Changze Cao; Rui Zhang; Mingfeng Zhao (Clinical and Translational Medicine, 2026)
Abstract To date, the treatment of acute myeloid leukaemia (AML) remains a major challenge in hematologic malignancies, particularly among elderly patients who are unfit for intensive chemotherapy. Venetoclax, a BCL‐2 inhibitor, in combination with azacitidine, has significantly improved the prognosis and survival of this patient population. However, approximately 30% of patients do not respond to venetoclax‐based combination regimens, and most initial responders eventually experience relapse. Therefore, resistance to venetoclax has become a critical bottleneck limiting its long‐term clinical benefits. A thorough understanding of the underlying resistance mechanisms and the development of novel strategies to overcome resistance are central to improving survival outcomes in elderly AML patients. The resistance mechanisms of venetoclax are complex and multifaceted, including genetic drivers such as TP53 mutations, FLT3‐ITD, and NRAS/KRAS mutations, as well as the upregulation of anti‐apoptotic proteins (e.g., MCL‐1, BCL‐xL), metabolic reprogramming, and altered cellular differentiation states. In response to these factors, emerging therapeutic strategies are rapidly evolving toward precision‐based and combination approaches, including combinations with targeted agents (e.g., IDH2 inhibitors, FLT3 inhibitors), MCL‐1 inhibitors, optimization of current dosing regimens (e.g., DEC3‐VEN), and the development of novel modalities (e.g., antibody‐drug conjugates, CAR‐T cell therapy). Focusing on the disease characteristics of elderly AML, this narrative review summarizes the clinical efficacy of venetoclax, critically examines the multifaceted mechanisms of venetoclax resistance, and discusses current and emerging therapeutic strategies to overcome this resistance. The goal is to inform clinical practice and guide future translational research. Key Points This review elucidates the current mechanism of action, therapeutic effects, and limitations of venetoclax, focusing on its use and combination regimens in the specific patient population of elderly individuals with AML who are not suitable for intensive therapy, as well as strategies to overcome resistance, and provides future perspectives for addressing venetoclax resistance.